2004
DOI: 10.1128/mcb.24.20.9079-9091.2004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor α Directs Peroxisome Proliferator-Activated Receptor α Signaling in the Transcriptional Control of Energy Metabolism in Cardiac and Skeletal Muscle

Abstract: Estrogen-related receptors (ERRs) are orphan nuclear receptors activated by the transcriptional coactivator peroxisome proliferator-activated receptor ␥ (PPAR␥) coactivator 1␣ (PGC-1␣), a critical regulator of cellular energy metabolism. However, metabolic target genes downstream of ERR␣ have not been well defined. To identify ERR␣-regulated pathways in tissues with high energy demand such as the heart, gene expression profiling was performed with primary neonatal cardiac myocytes overexpressing ERR␣. ERR␣ upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
367
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 437 publications
(387 citation statements)
references
References 51 publications
(84 reference statements)
17
367
2
1
Order By: Relevance
“…Cumulative evidences indicate that another ERR subtype, ERRa, plays significant roles in energy metabolism and mitochondrial biogenesis in certain target cells and tissues via direct regulation of genes involved in fatty acid oxidation, ERRb suppresses prostate cancer cell growth S Yu et al glucose metabolism, oxidative phosphorylation and mitochondrial fusion Huss et al, 2004;Schreiber et al, 2004;Wende et al, 2005;Soriano et al, 2006;Villena et al, 2007). Moreover, ectopic ERRa expression can promote lipid accumulation in primary cardiac myocytes (Huss et al, 2004), whereas its loss of function reduces body fat in ERRa-knockout mouse (Luo et al, 2003). In a recent expression profiling study of all 49 NRs in mouse tissues, ERRb is shown to be widely and rhythmically expressed in many organ systems, suggesting that ERRb together with other NRs are important in maintaining global basal metabolism under circadian control Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidences indicate that another ERR subtype, ERRa, plays significant roles in energy metabolism and mitochondrial biogenesis in certain target cells and tissues via direct regulation of genes involved in fatty acid oxidation, ERRb suppresses prostate cancer cell growth S Yu et al glucose metabolism, oxidative phosphorylation and mitochondrial fusion Huss et al, 2004;Schreiber et al, 2004;Wende et al, 2005;Soriano et al, 2006;Villena et al, 2007). Moreover, ectopic ERRa expression can promote lipid accumulation in primary cardiac myocytes (Huss et al, 2004), whereas its loss of function reduces body fat in ERRa-knockout mouse (Luo et al, 2003). In a recent expression profiling study of all 49 NRs in mouse tissues, ERRb is shown to be widely and rhythmically expressed in many organ systems, suggesting that ERRb together with other NRs are important in maintaining global basal metabolism under circadian control Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Northern blot hybridizations with random-primed 32 P-labeled cDNA probes were performed using QuikHyb (Stratagene). Real-time quantitative reverse transcription-PCR (RT-PCR) was performed as previously described (37) and results were normalized to the expression of 36B4. Mouse-specific primers used for RNA analysis may be found in supplemental materials Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…ERR␣ is ubiquitous among tissues of the developing embryo and adult (20 -22) and regulates an assortment of genes and physiological processes (23)(24)(25)(26). Like the ERs, ERR␣ binds to EREs but is capable of also binding an estrogen-related response element (ERRE) unique to the ERRs (27)(28)(29) in monomer or dimer form (30).…”
mentioning
confidence: 99%